Highly active Brønsted acidic silicon phosphate catalyst for direct conversion of glucose to levulinic acid in MIBK–water biphasic system - Bokade, Vijay; Moondra, Hitakshi; Niphadkar, Prashant (SN Applied Sciences, 2020)
Due to depletion of fossil fuel reserves and environmental concerns demand the utilization of other renewable feedstocks such as biomass which is available abundantly in different quantities throughout the world. Catalytic transformation of this biomass or biomass-derived products such as glucose to valuable platform biochemicals viz: levulinic acid (LA) is academically as well as industrially important reaction. In the present work, Silicon phosphates (SixPO4) catalysts viz: Si10PO4, Si20PO4, Si30PO4, and Si40PO4 having solely Brønsted acidic properties were prepared by wet impregnation of H3PO4 (10–40 wt%) on fumed silica followed by calcination at 550 °C for 10 h. The prepared catalysts were characterized by various techniques such as XRD; NH3-TPD; FTIR etc. Formation of silicon phosphate structure was found to depend on % of P loading and its interaction with silica. The acidic property of SixPO4 catalyst was characterized by NH3-TPD and Pyridine-IR, confirmed that catalyst has exclusively strong Brønsted acidity. A high LA yield of 81 mol% over Si30PO4 has achieved at an optimized reaction condition of 140 °C; 10 h in MIBK–water (9:1) biphasic system.